Analysis of Risk Factors for Obesity Incidence at Johar Baru Community Health Center, Central Jakarta - Ginting, Johannes Bastira; Suci, Tri (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Obesity is a major contributor to degenerative diseases and continues to show high prevalence. Identifying key risk factors is essential for targeted intervention. Objective: This study aimed to analyze the dominant risk factors for obesity at the Johar Baru Community Health Center, Central Jakarta. Methods: An observational analytic study with a cross-sectional design was conducted using secondary data. From a population of 102,647 individuals, 72,680 were included through total sampling. Data were analyzed using Chi-square tests and multiple logistic regression (enter method) with a significance level of 0.05. Results: Bivariate analysis showed that gender, lack of physical activity, high sugar and fat consumption, and low fruit and vegetable intake were significantly associated with obesity (p </ 0.05). Multivariate analysis identified gender as the strongest risk factor (OR = 12.912; p = 0.000). Conclusion: Gender, physical inactivity, excessive sugar and fat intake, and inadequate fruit and vegetable consumption were significantly linked to obesity. Gender emerged as the most dominant factor. These findings support the development of targeted interventions focusing on promoting balanced diets, regular physical activity, and awareness of dietary fat types to address obesity at the community level.